Spartan strong : what it takes to overcome every obstacle - Marshall, Bethany (Martial artist); Burton, Jessica (Obstacle course racer); Allen, Zac; Encinales, Andres (MJ, 2018)
Team KO, a group of Obstacle Course Racers and Martial Artists, featured on Spartan: Ultimate Team Challenge, band together to share their secrets to success in overcoming obstacles in both life and Obstacle Course Racing (OCR). By compiling their life struggles--cancer, addiction, and poverty--readers alike find relatable guidance to overcoming their own challenges. Spartan Strong introduces each team member--Bethany Marshall, Zac Allen, Jessica Burton, Andres Encinales--before identifying 19 qualities the team has used as essential tools to incorporate in everyday life. Each chapter includes an opportunity for immediate reader response in the form of a practical takeaway with an accompanying journal prompt. -- Publisher description.